KAJIAN KOMPARATIF KONFIGURASI RUANG Studi Kasus : Museum Nasional Indonesia, Museum MACAN, ART1:New Museum: Studi Kasus: Museum Nasional Indonesia, Museum MACAN, ART1:New Museum - nabila maharani saputra; R Siti Rukayah (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract: As a key cultural institution, the museum plays a vital role in education and recreation. However, its appeal and engagement among diverse visitor demographics remain uneven. While the fundamental function of museums persists, there is a growing need for advancement in the presentation of collections, spatial organization, and the provision of visitor-oriented facilities. This study seeks to examine the relationships, comparisons, and contrasts in architectural design and spatial organization within museums featuring diverse collection typologies. The primary objective is to assess spatial planning standards through the analysis of form, spatial arrangements, and the interplay between spaces and exhibited collections. A comparative methodology is employed, utilizing an analytical approach to three museums located in Jakarta: Museum Nasional Indonesia, Museum MACAN, and ART1: New Museum. Descriptive analysis focuses on spatial patterns, interrelationships between spaces, and the characteristics of the collections. Data is gathered through literature review and online observations. The findings of this research are anticipated to provide a comprehensive understanding of the similarities and divergences in museum spatial planning and offer architectural design recommendations that can enhance both the visitor experience and the functionality of museum spaces. Keyword: Museum, Architectural Design, Spatial Organization Abstrak: Museum sebagai institusi publik memiliki peran penting dalam pendidikan dan rekreasi, namun pemahaman dan daya tariknya terhadap pengunjung, khususnya dari berbagai kalangan usia, masih belum merata. Fungsi utama museum tetap konsisten, namun perkembangan dalam penyajian koleksi, pengaturan ruang, dan fasilitas yang mendukung pengalaman pengunjung sangat diperlukan. Penelitian ini bertujuan untuk menganalisis hubungan, perbandingan, dan perbedaan desain arsitektural dan organisasi ruang pada museum dengan tipologi koleksi yang beragam. Fokus utama penelitian adalah untuk mengevaluasi standar perencanaan tata ruang museum melalui studi bentuk, organisasi ruang, dan interaksi ruang dengan koleksi yang dipamerkan. Studi ini menggunakan metode komparasi dengan pendekatan analitis terhadap tiga museum yang ada di Jakarta, yakni Museum Nasional Indonesia, Museum MACAN, dan ART1: New Museum. Analisis dilakukan secara deskriptif terhadap pola tata ruang, hubungan antar ruang, dan karakteristik koleksi. Data diperoleh melalui studi literatur dan survey lapangan. Hasil penelitian ini diharapkan memberikan pemahaman yang mendalam tentang perbedaan dan kesamaan dalam perencanaan ruang museum, serta memberikan rekomendasi desain arsitektural yang dapat meningkatkan kualitas pengalaman pengunjung dan fungsionalitas ruang dalam museum. Kata Kunci: Museum, Desain Arsitektural, Organisasi Ruang